Inputs of Terrestrial Dissolved Organic Matter Enhance Bacterial Production and Methylmercury Formation in Oxic Coastal Water - Rodríguez, Juanjo; Andersson, Agneta; Björn, Erik; Timonen, Sari; Brugel, Sonia; Skrobonja, Aleksandra; Rowe, Owen (Frontiers in Microbiology, 2022)
Methylmercury (MeHg) is a potent neurotoxin commonly found in aquatic environments and primarily formed by microbial methylation of inorganic divalent mercury (Hg(II)) under anoxic conditions. Recent evidence, however, points to the production of MeHg also in oxic pelagic waters, but the magnitude and the drivers for this process remain unclear. Here, we performed a controlled experiment testing the hypothesis that inputs of terrestrial dissolved organic matter (tDOM) to coastal waters enhance MeHg formation via increased bacterial activity. Natural brackish seawater from a coastal area of the Baltic Sea was exposed to environmentally relevant levels of Hg(II) and additions of tDOM according to climate change scenarios. MeHg formation was observed to be coupled to elevated bacterial production rates, which in turn was linked to input levels of tDOM. The increased MeHg formation was, however, not coupled to any specific change in bacterial taxonomic composition nor to increased abundance of known Hg(II) methylation genes. Instead, we found that the abundance of genes for the overall bacterial carbon metabolism was higher under increased tDOM additions. The findings of this study may have important ecological implications in a changing global climate by pointing to the risk of increased exposure of MeHg to pelagic biota.